Gerakan Literasi Desa: Membaca Untuk Masa Depan - Adi Robih Setiana (CV. SINAR HOWUHOWU, 2026)
Literacy is a crucial foundation in building an empowered and sustainable society. The ability to read, write, and comprehend information serves not only as a basic skill but also as a key to improving the quality of human resources, economic empowerment, and social and political participation. The reality in Village X shows that the community's literacy rate is still low, indicated by limited reading facilities, low interest in reading, and a lack of mentoring from literacy workers. This condition motivated the implementation of a community service program titled